Tinjauan Cyberlaw terhadap Ancaman dan Strategi Penanggulangan Cybercrime - Zainudin Hasan; Aldi Yansah; Bagas Satria Wijaya; Rahmi Fitrinoviana Salsabila; Salsabila Brillianti Sarenc; Aqsal Azan Putra Salim (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
This research aims to undergo a careful cyberlaw review of cybercrime threats and strategies for dealing with cybercrime through a literature review approach. With a focus on in-depth analysis of various relevant literary sources, this research uses literary methods to explore the legal framework that regulates criminal acts in the digital realm. The research results highlight the need for consistency and adaptation in legal regulations to strengthen effectiveness in dealing with increasingly complex and growing cybercrime attacks.